Well-Being, PTSD, College Adjustment in Student Veterans With and Without Disabilities - Umucu, Emre; Chan, Fong; Lee, Beatrice; Brooks, Jessica; Reyes, Antonio; Mangadu, Thenral; Chiu, Chung-Yi; Ferreira-Pinto, Joao (Frontiers in Education, 2022)
We examined mediating effects of the pillars of well-being (i.e., positive emotion, engagement, relationships, meaning, and accomplishment) on the relationship between PTSD symptoms and college life adjustment for student veterans. We recruited 205 student veterans. Mediation analysis was conducted to test whether the pillars of well-being mediate the relationship between PTSD and college life adjustment. The results showed that positive emotion and accomplishment had mediating effects on the relationship between PTSD symptoms and college adjustment.